Perlindungan Hukum Internasional Tentang Konfik Perang Lintas Negara Antara Palestina Dan Israel - Seri Mughni Sulubara; Murthada Murthada; Zikrullah Zikrullah; Evi Lestaria; Darmika Sempena; Dea Humaira; Lenyta Mawaddah; Mawaddah Mawaddah; Mulyani Ulan Dari; Nadila Ulfa; Nanda Wulandari; Putra Bahgia; Rahmat Roza; Raika Supia; Yulistiana Dewi (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
The conflict between Palestine and Israel continues to this day. The problems that occur between the two countries, namely between the Palestinian state and Israel regarding the seizure of territory occur after years marked by violence until now so that there needs to be an effort to protect international law against war victims of innocent civilians. The theory used in this research is the theory of legal protection. The theory of legal protection is very relevant to the research made here, because there needs to be international legal protection regarding the conflict between Palestine and Israel. The research method used regarding the protection of international law on the conflict between Palestine and Israel is carried out by means of qualitative descriptive research. The technique or instrument of data collection used is library research by studying various books as literature, official documents, laws and regulations, results of previous research, and other literature sources related to the problems studied. Legal efforts made internationally against this war conflict include the UN Resolution in 1947, the Geneva Convention, the International Court of Justice (ICJ) and the Olso Agreement.